Ablation outcomes for atypical atrial flutter versus recurrent atrial fibrillation following index pulmonary vein isolation. (5th May 2021) - Akhtar, Tauseef; Daimee, Usama A.; Sivasambhu, Bhradeev; Boyle, Thomas A.; Arbab‐Zadeh, Armin; Marine, Joseph E.; Berger, Ronald; Calkins, Hugh; Spragg, David
Abstract: Background: Data related to electrophysiologic characteristics of atypical atrial flutter (AFL) following atrial fibrillation (AF) ablation and its prognostic value on repeat ablation success are limited. Methods: We studied consecutive patients who underwent a repeat left atrial (LA) ablation procedure for either recurrent AF or atypical AFL, at least 3 months after index AF ablation, between January 2012 and July 2019. The demographics, clinical history, procedural data, complications, and 1‐year arrhythmia‐free survival rates were recorded for each subject after the first repeat ablation. Results: A total of 336 patients were included in our study. Among these 336 patients, 102 underwent a repeat ablation procedure for atypical AFL and 234 underwent a repeat ablation procedure for recurrent AF. The mean age was 63.7 ± 10.7 years, and 72.6% of patients were men. The atypical AFL cohort had significantly higher LA diameters (4.6 vs. 4.4 cm, p  = .04) and LA volume indices (LAVi; 85.1 vs. 75.4 ml/m 2, p  = .03) compared to AF patients at repeat ablation. Atypical AFL patients were more likely to have had index radiofrequency (RF) ablation (as opposed to cryoballoon) than recurrent AF patients (98% vs. 81%, p  = .01). Atypical AFLs were roof‐dependent in 35.6% and peri‐mitral in 23.8% of cases. Major complications at repeat ablation occurred in 0.9% of the total cohort. Arrhythmia‐free survival at one year was significantly higher in the recurrent atypical AFL compared to the recurrent AF cohort (75.5 vs. 65.0%, p  = .04). Conclusion: In our series, roof‐dependent flutter is the most common form of atypical atrial flutter post AF ablation. Patients developing atypical AFL after index AF ablation have greater LA dimensions than patients with recurrent AF. The success rate of first repeat ablation is significantly higher among patients with recurrent atypical AFL as compared to recurrent AF after index AF ablation.